1994
DOI: 10.1111/j.1745-4557.1994.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pasteurization or Sodium Benzoate on Long‐term Storage Stability of Peach Puree

Abstract: The effect of long-term storage on the stabiliry ofpasteurized (PA) or sodium benzoate (SB) (0.1 X) treated peach puree was studied. Color, viscosity, soluble solids, pH, titratable acidity, sugars and organic acids were monitored over 4 months. Yeasts were the major microorganisms causing spoilage in nontreated peach puree. Storage at 2C increased the holding time of the control to 17 days compared with 3 days at 2SC. No yeast or other microorganisms were found in PA or SB treated puree held at 2 and 25C, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Robertson et al (1990) determined a maximum storage life of 4 weeks at 0 °C for fresh peaches prior to quality deterioration, while Gorney et al (1999) showed that ascorbic acid, calcium lactate, and modified atmospheres were marginal in extending the shelf life of fresh-cut peaches. Residual polyphenoloxidase (PPO) activity was hypothesized to cause a decrease in color characteristics in partially processed peach puree during storage (Bian et al, 1994), while nonenzymatic browning in pasteurized peach purees was attributed to reducing the extent of sugar degradation and HMF formation (Garza et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Robertson et al (1990) determined a maximum storage life of 4 weeks at 0 °C for fresh peaches prior to quality deterioration, while Gorney et al (1999) showed that ascorbic acid, calcium lactate, and modified atmospheres were marginal in extending the shelf life of fresh-cut peaches. Residual polyphenoloxidase (PPO) activity was hypothesized to cause a decrease in color characteristics in partially processed peach puree during storage (Bian et al, 1994), while nonenzymatic browning in pasteurized peach purees was attributed to reducing the extent of sugar degradation and HMF formation (Garza et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned results could be interpreted by the findings of Bian et al, [35], which they found that the total sugar level and soluble sugars of peach puree did not change with either pasteurized or sodium benzoate treatments. However, thermal pre-treatments showed a Table 5: Effect of enzymes pre-treatments and incubation on different parameters of color characteristics and non-enzymatic browning (A 420 nm) of pumpkin juice.…”
Section: Effect Of Pre-treatments (Thermal and Enzymes) And Incubatiomentioning
confidence: 70%
“…Effect of pre-treatments (thermal and enzymes) and incubation on Sugar compositions of pumpkin juice (sugar profile): Sucrose, glucose and fructose were the major soluble neutral sugars and predominant sugar found in the incubated, untreated and treated pumpkin juice samples, Furthermore, Bian et al, [35] found similar results in peach puree. Glucose contents were relatively higher than sucrose and fructose contents in fresh pumpkin juice samples ( Table 6).…”
Section: Effect Of Pre-treatments (Thermal and Enzymes) And Incubatiomentioning
confidence: 83%
“…However, P3, P4, P5, P6 and P7samples stored at ambient conditions, the TSS content shows a significant increase generally throughout the storage period. Unpeeled (P0) and peeled (P1) samples show the gradual decrease in total soluble solids towards the end of the storage period (30–45 days) and the decrease is statistically significant, which can be related to the fact that fungal growth can use sugars for metabolism thus can decrease TSS during later stages of storage ( Bian et al., 1994 ). While as the purees treated with 10% sugar and 15% sugar with KMS treatments does not show any decrease in TSS during the whole storage period, which may be due to the presence of preservatives.…”
Section: Resultsmentioning
confidence: 99%